High oxalate concentrations correlate with increased risk for sudden cardiac death in dialysis patients - Pfau, Anja; Ermer, Theresa; Coca, Steven G.; Tio, Maria Clarissa; Genser, Bernd; Reichel, Martin; Finkelstein, Fredric O.; März, Winfried; Wanner, Christoph; Waikar, Sushrut S.; Eckardt, Kai-Uwe; Aronson, Peter S.; et al. (Journal of the American Society of Nephrology, 2021)
Background The clinical significance of accumulating toxic terminal metabolites such as oxalate in patients with kidney failure is not well understood. Methods To evaluate serum oxalate concentrations and risk of all-cause mortality and cardiovascular events in a cohort of patients with kidney failure requiring chronic dialysis, we performed a post-hoc analysis of the randomized German Diabetes Dialysis (4D) Study; this study included 1255 European patients on hemodialysis with diabetes followed-up for a median of 4 years. The results obtained via Cox proportional hazards models were confirmed by competing risk regression and restricted cubic spline modeling in the 4D Study cohort and validated in a separate cohort of 104 US patients on dialysis after a median follow-up of 2.5 years. Results A total of 1108 patients had baseline oxalate measurements,with a median oxalate concentration of 42.4 μM.During follow-up, 548patients died, including139 (25.4%) fromsudden cardiac death.Atotal of 413 patients reached the primary composite cardiovascular end point (cardiac death, nonfatalmyocardial infarction, and fatal or nonfatal stroke). Patients in the highest oxalate quartile (≥59.7 μM) had a 40%increased risk for cardiovascular events (adjusted hazard ratio [aHR], 1.40; 95% confidence interval [95% CI], 1.08 to 1.81) and a 62% increased risk of sudden cardiac death (aHR, 1.62; 95% CI, 1.03 to 2.56), compared with those in the lowest quartile ( ≤ 29.6 mM). The associations remained when accounting for competing risks and with oxalate as a continuous variable. Conclusions Elevated serumoxalate is a novel risk factor for cardiovascular events and sudden cardiac death inpatients ondialysis. Further studies arewarranted to testwhether oxalate-lowering strategies improve cardiovascular mortality in patients on dialysis.
CRIS-Team Scopus Importer:2021-09-17